Дослідження підводно-археологічної експедиції біля південного узбережжя Криму - Воронов, С.О. (Археологічні дослідження в Україні, 2010)
The information on deep-water research of the Department of Underwater Heritage of the IA NASU in 2009 is presented. Two objects have been discovered: a large sailing and rowing vessel of the 12th and 13th centuries and the remains of a commercial sailing vessel of the 18th and 19th centuries. Further study of these objects is planned.